English for International Relations: Vocabulary Grammar and Translation Practice - Плетенецька, Юлія Миколаївна (Taras Shevchenko National University of Kyiv, 2026)
The present textbook, English for International Relations: Vocabulary, Grammar and Translation Practice has been designed as a modern and relevant resource for first-year students majoring in International Relations who are pursuing a dual qualification as translators of two foreign languages. It reflects current methodological approaches to language teaching in professional contexts and addresses the growing need for integrated linguistic and translation training. The structure of the book is clear and pedagogically sound. It consists of two main sections—lexical and grammatical practice—each of which is complemented by a variety of translation-oriented tasks. This integrated approach ensures that students not only consolidate their knowledge of vocabulary and grammar, but also develop practical translation skills essential for their future professional activities. A distinctive feature of the coursebook is the wide range of carefully selected exercises aimed at reinforcing key language topics in alignment with the core textbook of the course, English for International Relations. In this way, the manual both enriches and expands the primary learning material, ensuring continuity in the learning process. At the same time, it can be effectively used as an independent instructional resource or as a supplementary tool within the broader course framework. Particular attention is given to the development of translation competence. The book offers diverse tasks that foster skills in consecutive and simultaneous interpreting, as well as sight translation. Importantly, many of the translation exercises are based on original texts drawn from contemporary media sources. The use of authentic English-language materials of political and analytical nature enables students to engage with current issues in international relations and diplomacy, enhances their critical thinking, and cultivates their ability to respond promptly and appropriately to professional communicative challenges. While the coursebook occasionally includes a relatively large number of complex text-based exercises, which may present a certain challenge for beginners, this aspect can be effectively managed through a differentiated instructional approach. Both in-class and independent work can be adapted to students’ proficiency levels, thereby turning this feature into an advantage that promotes deeper comprehension and mastery of the material. In light of the above, this coursebook meets the standards required of educational publications of its kind. It is well-suited for implementation in the academic process and can be confidently recommended for publication and use in higher education institutions.
Keywords: English